Qhali: A Humanoid Robot for Assisting in Mental Health Treatment - (:unkn) unknown (MDPI, 2024)
In recent years, social assistive robots have gained significant acceptance in healthcare settings, particularly for tasks such as patient care and monitoring. This paper offers a comprehensive overview of the expressive humanoid robot, Qhali, with a foc...
Keywords: Robots humanoides; Salud mental